## anonymous one year ago solving systems of equations by elimination -x + 9y = -5 x - 5y = 1

• This Question is Open
1. haleyelizabeth2017

Add the second equation to the first equation to get 4y=-4

2. haleyelizabeth2017

Then, divide -4 by 4 to get y=-1. Plug in -1 for y into either equation and solve for x.

3. haleyelizabeth2017

x-5y=1 x-5(-1)=1 x+5=1 x=-4

4. haleyelizabeth2017

Then plug x and y back into either equation to check your answer.

5. anonymous

do i add or subtract them

6. haleyelizabeth2017

7. anonymous

ty :D

8. haleyelizabeth2017

No problem!

9. anonymous

-4+-1

10. anonymous

with will be -5

11. anonymous

whitch*

12. haleyelizabeth2017

Wait..

13. haleyelizabeth2017

-(-4) + 9(-1) = -5 (-4) - 5(-1) = 1 Plug them into these equations to check

14. anonymous

omg im new too this subject lol like ugh

15. haleyelizabeth2017

haha don't worry about it, you'll get the hang of it!

16. haleyelizabeth2017

just know...the solution would be (-4, -1)

17. anonymous

for the answer right ill let you kno if i need help on the next one

18. haleyelizabeth2017

Okay

19. haleyelizabeth2017

Did you understand how I got that?

20. anonymous

thanks again

21. haleyelizabeth2017

No problem!

22. anonymous

y = 2/3x-1 y=3

23. anonymous

y = 2/3x-1 y=3

24. haleyelizabeth2017

are those the two equations given?

25. anonymous

yes

26. haleyelizabeth2017

okay, so 3=2/3x-1 y is given so we have (_, 3) so far.

27. anonymous

ok

28. haleyelizabeth2017

3+1=2/3x 4=2/3x 4*3/2=x x=6 so (6, 3) :)

29. anonymous

THANKS!

30. haleyelizabeth2017

No problem!

31. anonymous

8 more to go idk if you going to help me with all this lmao